Pengaruh frekuensi ultrasonik terhadap mortalitas serangga perusak kayu Dinoderus minutus Fabricius (Coleoptera: Bostrichidae) - Susanti, Etik; Wiranto, Aryo Seto Pandu; Ismanto, Agus; Soesilohadi, RC Hidayat (Jurnal Entomologi Indonesia, 2022)
Dinoderus minutus Fabricius (Coleoptera: Bostrichidae) is one of the main pests of wood and bamboo borer. Control of these insects is still dependent on the use of insecticides. This study is a preliminary test for the use of ultrasound frequency as a pest control agent. The research aims to study the effect of ultrasonic frequencies on D. minutus mortality. The method used exposure of ultrasonic frequency to imago D. minutus for 7 days and 14 days indoors with temperatures of 28 °C to 29 °C and humidity of 70% to 81%. Significant results for the ultrasonic frequency treatment which resulted in a D. minutus mortality of 80.00% with a duration of 14 days exposure. The results show that ultrasound frequency with the exact durations can be used as a form of D. minutus control.